A response to decentralised governance of human rights: a Children's Rights Approach in Wales - RHIAN CHAMBERLAIN (The International Journal of Human Rights, 2023)
The dominant arrangement for governance in many States which are party to international human rights treaties is decentralisation. This puts implementation of human rights in the hands of institutions which are geographically closer to intended beneficiaries. Decentralisation to different levels of government introduces complexity, risk and opportunity to the governance of human rights. In response, UN Treaty Monitoring Bodies focus on State responsibility for implementation of human rights. The Committee on the Rights of the Child has emphasised the State as the coordinating body responsible for children's rights under the UN Convention on the Rights of the Child (CRC). In this paper, Wales is used as an example of a jurisdiction where decentralisation is a feature of children's rights, which has enabled a progressive approach to implementation. It explains the principled Children's Rights Approach which provides public authorities in Wales with a coherent framework to give effect to international children's rights policy planning and service delivery. As the contours of decentralisation in Wales are typical of arrangements in many States parties to the CRC, insights from Wales will be transferable to other jurisdictions. This experience is also relevant to other areas of human rights implementation in the context of decentralisation.